A Modified Combination Rule for D Numbers Theory. (29th November 2016) - Wang, Ningkui; Liu, Fuyu; Wei, Daijun
Abstract : D numbers theory is an appropriate method to deal with the information of uncertainty and incompleteness when making a reasonable decision. PreviousD numbers theory provides a rule to combine multipleD numbers. However, the commutative law is not satisfied in the rule of combining multipleD numbers. In this paper, a modified method for multipleD numbers combination is proposed. The proposed method defines a new function for multipleD numbers combination which is mainly determined by the original value ofD numbers. Then the proposed combination rule is applied to environmental impact assessment (EIA); our results show that the proposed method is efficient for multipleD numbers combination and it is useful when dealing with uncertainty and incompleteness.